Trainer expertise in business training: evidence from the Sri Lankan Microfinance Institutions - Abeysekera, Ruwan (Management and Entrepreneurship: Trends of Development, 2020)
Microfinance Institutions (MFIs) provide business training to its clients in order to improve their knowledge and skills so that they can manage their businesses effectively and efficiently. MFIs can also experience better loan repayment rates due to the provision of business training. Thus, business training is important to both MFIs and clients. To deliver business training successfully, the expertise of the trainers matters significantly. Hence, the objectives of this study are to define the expertise, to identify how expertise could help clients in their business ventures, and to identify strategies used by trainers to transfer their expertise. The case study method was used to carry out this study and six Sri Lankan MFIs were used as cases. One manager, one trainer, and one owner manager/client from each MFI were selected for interviews and hence, 18 in depth interviews were conducted to gather data. The findings reveal that the trainers’ expertise consists of business knowledge and experiential knowledge. Trainers use business knowledge to provide subject knowledge such as financial literacy and business plan preparation. Experiential knowledge is used to create networking opportunities and to provide subject knowledge as well. Further, the trainers use strategies such as interactive training and communication to transfer the expertise. The findings of this study would be useful to microfinance practitioners, policy makers, and it further contributes to the knowledge domain of microfinance. JEL Classification: M10